Theoretical Aspect of Diagonal Bregman Proximal Methods - S. Kabbadj (Journal of Applied Mathematics)
In this paper, we propose and study a diagonal inexact version of Bregman proximal methods, to solve convex optimization problems with and without constraints. The proposed method forms a unified framework for existing algorithms by providing others.